-(4xy-12)+4(4xy+4)=

Simple and best practice solution for -(4xy-12)+4(4xy+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(4xy-12)+4(4xy+4)= equation:


Simplifying
-1(4xy + -12) + 4(4xy + 4) = 0

Reorder the terms:
-1(-12 + 4xy) + 4(4xy + 4) = 0
(-12 * -1 + 4xy * -1) + 4(4xy + 4) = 0
(12 + -4xy) + 4(4xy + 4) = 0

Reorder the terms:
12 + -4xy + 4(4 + 4xy) = 0
12 + -4xy + (4 * 4 + 4xy * 4) = 0
12 + -4xy + (16 + 16xy) = 0

Reorder the terms:
12 + 16 + -4xy + 16xy = 0

Combine like terms: 12 + 16 = 28
28 + -4xy + 16xy = 0

Combine like terms: -4xy + 16xy = 12xy
28 + 12xy = 0

Solving
28 + 12xy = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + 12xy = 0 + -28

Combine like terms: 28 + -28 = 0
0 + 12xy = 0 + -28
12xy = 0 + -28

Combine like terms: 0 + -28 = -28
12xy = -28

Divide each side by '12y'.
x = -2.333333333y-1

Simplifying
x = -2.333333333y-1

See similar equations:

| 3(4+6)=9X+12 | | -(7xy-8)+4(3xy+5)= | | -(5xy-9)+4(3xt+4)= | | 6(z-2)+6z-4= | | -2x-50=0 | | 4r-7r+9r= | | -2x/7+9=435/49 | | -2x-50=-640 | | x=(49/12) | | 4(7x-5/6)=-514/3 | | 2/7(1/2+5x)=71/7 | | 5/8+2x/3=21/8 | | graphx=5 | | 2y-7+3y-7= | | -x/7+3/8=29/56 | | 2y-5+4y-9= | | y=-3.9x+2.8 | | 6x-5/5=-7 | | 9x/16=81 | | 3/5+x=3/5 | | 1/2-3x/5=-11/2 | | X-1/2=-13/2 | | Y+-14=9 | | 5/6t+2/3t=45 | | 5x-8/4=7 | | (15x^4y^5/18x^6y)/(25x^12y^4/12x^5y^4) | | -5x/7+9=33/7 | | 5/8+7x=117/8 | | -2(7x+4)= | | 15+6*7+x=88 | | B=9/8(j-65) | | 3h+5=50 |

Equations solver categories